Dividends policy and profitability in businesses - Santos Jiménez, Néstor (2008)
The companies, of the financial point of view, to increase to the maximum the value of the representative actions of their social capital, look for to coordinate their financial decisions as for the investment, financing and dividends. The politics of dividends, be cash the money and/or in the additional actions about utilities, it is strong in the perception of the value of market of the company. The practical evidence of the politics’s of dividends effect in the value of the actions of the company, is presented, for a sample of four companies of generation electric maidservant: ELECTROPERU, EDEGEL, ENERSUR AND EGENOR. The energy production for these companies in the year 2006, according to the Committee of Economic Operation of the Electric Sector (COES) it represented 75% of the production of the National Cruz-trigger the Electric System. The four companies have the politics of dividends that the you/they keeps certain similarity, and of who the application in each fiscal exercise depends on the plans of growth and/or of optimization of passive that apply.